Comparing Mechanical Characterization of Carbon, Kevlar, and Hybrid-Fiber-Reinforced Concrete under Quasistatic and Dynamic Loadings - Yeou-Fong Li; Kun-Han Yang; Pei-Yao Hsu; Jin-Yuan Syu; Shea-Jue Wang; Wen-Shyong Kuo; Ying-Kuan Tsai (Buildings, 2023)
Concrete is a brittle material due to its poor tensile strength; consequently, concrete tends to crack or peel under an applied external load. Previous studies have investigated the effect of incorporating fiber into concrete, which can improve its tensile strength. In this study, the static and dynamic mechanical characteristics of three types of fiber-reinforced concrete (FRC) were examined: carbon-fiber-reinforced concrete (CFRC); Kevlar-fiber-reinforced concrete (KFRC); and a combination of both, known as carbon/Kevlar-hybrid-fiber-reinforced concrete (HFRC). This study created concrete specimens by pneumatically dispersing carbon and Kevlar fibers and mixing them with cement to comprise 1% of the weight. The mixture was then combined with aggregates and water to form the concrete specimens. When compared with the benchmark concrete specimens, it was found that the compressive strength of the CFRC, KFRC, and HFRC specimens increased by about 19% to 50%, the bending strength increase by about 8% to 32%, and the splitting strength increased by about 4% to 36%. Specifically, the HFRC made with the 24 mm carbon and Kevlar fibers displayed the most significant mechanical strength in a static state. Furthermore, the HFRC showed superior resistance to impact compared to the benchmark concrete specimens across various impact energies, with the 24 mm carbon and Kevlar fiber HFRC showing the highest resistance. The inclusion of fibers in the split Hopkinson pressure bar (SHPB) test demonstrated a notable increase in the maximum strength, particularly in the case of the 12 mm carbon fiber combined with the 24 mm Kevlar fiber in the HFRC specimen.